Characterization and mechanism analysis of interaction between Inconel 713C superalloy and a novel crucible-shell "integrated" mold. (March 2023) - Wang, Shuo; Du, Ming; Jin, Yu; Li, Qingling; Li, Jinpeng; Zhang, Huarui; Zhang, Hu; Cheng, Ying
Abstract: A novel crucible-shell "integrated" mold for rapid preparation of supercharged turbines was quantitatively characterized, and the interaction mechanism between refractory and melt was systematically analyzed. The results show that Inconel 713C superalloy is not easy to react with aluminum silicate fiber crucible, and the interaction between them is physical penetration. At the same time, the slag balls in the crucible are easy to peel off into the alloy and form inclusions. The reaction between Inconel 713C superalloy and shell surface material (ZrSiO4 ) can be divided into Penetration, Stalling/dissolution, Reaction and Diffusion stages. The interface reaction layer is composed of Nb2 O5, Al2 O3, ZrO2, Cr2 O3 and TiO2 . The oxide elements produced by the reaction come from the alloy and ceramic shell. Compared with the traditional preparation of turbocharger turbine under discontinuous vacuum, the use of "integrated" mold to prepare turbine under continuous vacuum environment reduces the oxygen, nitrogen and hydrogen content of castings, and the purity of Inconel 713C superalloy is higher and the preparation time is faster, which is conducive to industrial production, which can shed new lights on choosing alternative refractory material for the rapid preparation of high-purity superalloys. Highlights: A novel crucible-shell "integrated" mold and its influence on Inconel 713C superalloy's purity were systematically characterized for the first time. The interaction between alloy and aluminum silicate fiber crucible mainly exists as physical exfoliation of aluminum silicate fibers and slag balls. The interaction between alloy and ZrSO4 shell can be divided into penetration, spalling/dissolution, reaction and diffusion stages. High purity Inconel 713C superalloy was successfully obtained by preparation under continuous vacuum condition.